(untitled) - Barry, Eugene F. (Hoboken, N.J., 2007)
Gas Chromatography (GC) is the most widely used method for separating and analyzing a wide variety of organic compounds and gases. There have been many recent advancements in both packed column and capillary column GC. With numerous options and considerations, selecting the right column can be complicated. This resource provides essential guidance for scientists and technicians, including: Methods of choosing both capillary and packed columns. Selection of dimensions (column length, I.D., film thickness, etc.) and type of column. Guidelines for proper connections of the column to the injector and detector,...
Keywords: Gas chromatography,Phép sắc kí chất khí